2014
DOI: 10.1007/s12325-014-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Asenapine in the Treatment of Patients with Bipolar I Disorder with Mixed Episodes in an Italian Context

Abstract: IntroductionBipolar disorder is a chronic disease characterized by periods of mania or hypomania, depression, or a combination of both (mixed state). Because bipolar disorder is one of the leading causes of disability, it represents an important economic burden on society. Asenapine (ASE) is a new second-generation antipsychotic developed and approved for the treatment of manic or mixed episodes associated with bipolar disorder. The objective of the present study was to assess the cost-effectiveness of ASE com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This was primarily driven by an earlier response to asenapine [ 57 ]. This model was adapted for use in another study that aimed to estimate the cost effectiveness of asenapine compared with olanzapine in the treatment of patients with bipolar I disorder and a current manic episode in the context of Italian National Health Service [ 58 ]. Asenapine was found to be associated with lower direct costs, which was mostly due to the savings from hospitalisations avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was primarily driven by an earlier response to asenapine [ 57 ]. This model was adapted for use in another study that aimed to estimate the cost effectiveness of asenapine compared with olanzapine in the treatment of patients with bipolar I disorder and a current manic episode in the context of Italian National Health Service [ 58 ]. Asenapine was found to be associated with lower direct costs, which was mostly due to the savings from hospitalisations avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Asenapine was found to be associated with lower direct costs, which was mostly due to the savings from hospitalisations avoided. Asenapine was also associated with higher quality of life compared with olanzapine [ 58 ]. The cost effectiveness of asenapine therapy for mania in patients with bipolar I disorder was also evaluated in the context of Canadian practice, using a decision-tree account of the probability of extrapyramidal symptoms, switching to a different antipsychotic drug and gaining weight, and the Markov model to account for long-term metabolic complications such as diabetes, hypertension, coronary heart disease and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Asenapine use was also associated with the prevention of psychiatric hospitalizations, generating a better quality of life, and more quality-adjusted life-years. 31 , 45 , 46 However, cost benefits were not found in one Spanish study which researched a 6-month naturalistic treatment with adjunctive asenapine vs other adjunctive antipsychotics. 23 In a post-hoc analysis of two acute trials in BD-I patients with mixed episodes, asenapine users found improved health-related quality of life compared to olanzapine and placebo-treated patients.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Actually, during the registration phase, the efficacy and tolerability of asenapine was evaluated in both monotherapy and in association with another mood stabilizer, such as lithium or valproate, a rather common scenario in the clinical practice, in order to verify its safety in the long‐term use . In any case, the information on this topic is still limited to that, however, would indicate adjunctive asenapine in BD is effective and safe .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, during the registration phase, the efficacy and tolerability of asenapine was evaluated in both monotherapy and in association with another mood stabilizer, such as lithium or valproate, a rather common scenario in the clinical practice, in order to verify its safety in the long-term use [25]. In any case, the information on this topic is still limited to [18,[29][30][31][32][33] that, however, would indicate adjunctive asenapine in BD is effective and safe [30]. Therefore, given the paucity of available information, the aim of this study was to present some case reports of BD patients treated acutely with asenapine as add-on treatment, and followed up for 2 years.…”
Section: Introductionmentioning
confidence: 99%